A Case Study on Structural Failure of Reinforced Concrete Beam-Column Joint After the First Significant Earthquake Impact in Malaysia - Ganasan, Reventheran; Tan, Chee Ghuan; Ibrahim, Zainah; Mohamed Nazri, Fadzli; Wong, Yew Hoong (International Journal of Integrated Engineering, 2020)
This paper presents a case study regarding failures of structural buildings which occurred in Malaysia after the first significant earthquake event dated on June 5, 2015. Ranau is a locality situated in Sabah, Malaysia on the island of Borneo. The seismic activity was triggered when an earthquake with a magnitude of 5.9 afflicted Ranau, including seven other districts that also felt the tremors. Even though the impact of magnitude was undisputedly not high, the severity level of damages was found to be absolute (irreparable) in the structural RC beam-column joints and soft-storey buildings. Most of the buildings in Malaysia were built without the consideration of seismic design, and thus a major factor in structural failure. The earthquake has directed the seismic demand, while the total displacement was concentrated at the weakest floor that caused more damage to the building.  This paper shows the causes of beam-column joint damages and explains the proposed (to-date) strengthening methods. Future studies related to seismic activities are in need to analyse the performance of the existing design of structural RC members and propose a seismic design in Malaysia.